The implementation of reality counseling to overcome students' isolated behavior - Zuhara, Evi; Mahdayani, Mahdayani (ProGCouns: Journal of Professionals in Guidance and Counseling, 2022)
Individuals who are identified with an isolated behavior tend to have inferior behavior that they may have difficulty to socialize properly and adapt to their group. T eenagers with this behavior also tend to interact passively by showing a lack of engagement with other people. This study aims to examine reality counseling to overcome the isolated behavior in teen students. This study used a One Group Pretest-Postest design of experiment, involving 10th grader students as many as 5 out of 53 students. Students were given a Likert Scale questionnaire before and after the treatment of the reality counseling. The result shows that reality counseling had a contribution to the improvement of the isolated behavior. The average score increases by 30.400 in pretest and post-test results, from 91.00 to 122.00. This study reveals that reality counseling could be used to overcome students' isolated behavior. This means students show an increase in social interest in every aspect, such as inferior students trying to interact with other people and build self-confidence, domineering students start to change their perception by not comparing their ability to someone's ability. In additon, selfish students were able to control their emotion and students who like to be alone could try to get along with their friends.